Realizing Stretchable OLEDs: A Hybrid Platform Based on Rigid Island Arrays on a Stress‐Relieving Bilayer Structure. Issue 11 (16th August 2020) - Kim, Taehyun; Lee, Hyeonwoo; Jo, Woosung; Kim, Taek‐Soo; Yoo, Seunghyup
Abstract: Optoelectronic devices that are stretchable can revolutionize various fields by enabling the functionalities that are not accessible from conventional rigid platforms. In this respect, many efforts are made to realize stretchable organic light‐emitting diodes (OLEDs) for their compatibility with various deformable substrates. Two representative examples of such efforts include a method based on intrinsically stretchable materials and a method to attach ultrathin OLEDs on a prestrained elastomer substrate. However, both of those methods have limitations either in material availability for high performance or in optical clarity. Here a hybrid platform is proposed for stretchable OLEDs free from such limitations. The proposed platform is composed of an array of rigid islands connected by serpentine‐shaped interconnectors formed on a bilayer elastomer substrate in which the top layer has an ultralow Young's modulus of ≈0.9 kPa, greatly relieving the rigid islands and interconnectors of the mechanical stress applied to them when stretched. With the proposed platform, stretchable OLEDs are demonstrated that can be repeatedly stretched by 140% and are based on thermally evaporable materials well established for fabrication of high‐performance OLEDs. Abstract : Here a hybrid platform, composed of an array of rigid islands connected by serpentine‐shaped interconnectors that are formed on a bilayer elastomer substrate, is proposed in which the top layer has an ultralow modulus, greatly relieving the mechanical stress applied to them when stretched. With the proposed platform, stretchable organic light‐emitting diodes (OLEDs) are demonstrated that can be repeatedly stretched by 140%.